SIMULASI PERBANDINGAN TEGANGAN STATIS KOMPONEN PINTU MOBIL BERBAHAN ALUMINIUM DAN KOMPOSIT BAMBU - Hasan Tjahaya; Agustinus Purna Irawan (Program Studi Teknik Mesin Universitas Tarumanagara, 2021)
The car door is one of the important components in a car, as a means of getting in and out of passengers and goods. This study aims to compare the factors of safety, strength, shear stress, and dimensional changes due to the received load, between car doors made of bamboo composite material and car doors made of aluminum. The research method is carried out in the form of simulating the load on the car door using Fusion Autodesk 360 software. The data used in this study is secondary data obtained from data analysis from journal articles related to bamboo and aluminum fiber composite materials. Strength simulation using loads of 100 N, 150 N, and 200 N refers to the strength simulation reference. Based on the simulation results, it can be concluded that the car door made of bamboo composite has good yield strength, safety factor, and shear strength and has the potential to be an alternative material to replace aluminum car doors, especially at low loads. The results of modeling using software with the above load, the safety factor values are in the range (10-15) and the displacement is in the range (3-4) mm. The results of this simulation become one of the references in further research and development.